Description of Chelisoches chongqingensis sp. nov. (Dermaptera: Chelisochidae) and redescription of Platylabia major Dohrn, 1867 from China - Ye, Xiao-Han; Gu, Jun; Zhang, Mei; Chen, Zhi-Teng (Zootaxa, 2020)
A new earwig species of Chelisoches Scudder, 1876, C. chongqingensis Ye & Chen sp. nov. is reported from Chongqin City of China. The new species is characterized by the distinct metallic luster on the elytra and by the pygidium shape of the female. Descriptions and illustrations of both the male and female of the new species are provided. Another species, Platylabia major Dohrn, 1867, is redescribed based on material collected from Guangdong and Fujian provinces.